Working their way to school completion: a snapshot of School-based Apprenticeships and Traineeships for young Australians. (2nd October 2017) - Klatt, Malgorzata; Clarke, Kira; Dulfer, Nicky
Abstract: This paper highlights troubling patterns within the Australian School-based Apprenticeships and Traineeships (SBATs) by analysing statistical data of 21, 000 of 15–19 year old apprenticeship/traineeship learners engaged in Vocational Education and Training in School (VETiS). It confirms the alignment of social groups to certain qualification fields and levels and provides a compelling picture of the learner profile of SBAT including the type of occupations and qualifications being undertaken at school level. In a complex policy environment, where VET in Schools has been assigned the important task of preparing 'workforce job-ready' students for the 'high skill and high earning roles our economy demands', we argue that the SBAT pathway is not yet adequate to meet these high expectations. It is not an effective apprenticeship pathway as it potentially 'locks-in' already disadvantaged young people to precarious pathways, and reinforces the nature of an already highly gender-segregated Australian labour market. The paper helps to focus attention on endemic weaknesses in the Australian VET system that serve to entrench disadvantage in Australian society.